Ten principles to integrate the water-energy-land nexus with climate services for co-producing local and regional integrated assessments - Cremades, Roger; Mitter, Hermine; Tudose, Nicu Constantin; Sanchez-Plaza, Anabel; Graves, Anil; Broekman, Annelies; Bender, Steffen; Giupponi, Carlo; Koundouri, Phoebe; Bahri, Muhamad; Cheval, Sorin; Cortekar, Jörg; et al. (Cranfield University, 2019)
The water-energy-land nexus requires long-sighted approaches that help avoid maladaptive pathways to ensure its promise to deliver insights and tools that improve policy-making. Climate services can form the foundation to avoid myopia in nexus studies by providing information about how climate change will alter the balance of nexus resources and the nature of their interactions. Nexus studies can help climate services by providing information about the implications of climate-informed decisions for other economic sectors across nexus resources. First-of-its-kind guidance is provided to combine nexus studies and climate services. The guidance consists of ten principles and a visual guide, which are discussed together with questions to compare diverse case studies and with examples to support the application of the principles.
Keywords: Stakeholder; Climate change; Multilayer network; Co-production; Nexus; Climate services